The Implementation Of Song Using Game Media To Improve Vocabulary Teaching In Islamic Senior High School: A Case Study At Islamic Senior High School In Ciamis - Chairanie, Dhea; Herlina, Rina (Journal of English Education Program (JEEP), 2024)
The study also connects the implementation of songs in a game to increase students' English vocabulary mastery skills. The purpose of the present study is to investigate the student’s motivation in learning English vocabulary. Mainly, the study is aimed to find out 1) elements influence students' willingness to listen to songs as a means of learning English; 2) the way the students acquire vocabulary knowledge related to students writing achievement in English subjects; and 3) teacher's opinion about the use of song using game media in the classroom. The study employs the qualitative paradigm with the type of case study at which the data were collected through observation and interviews. The participants of this study are students of class XII (11 students) in an Islamic Senior High School in Ciamis. The results show that there are elements influence students' willingness to listen to songs as a means of learning English such as facilities and infrastructure in schools and subject matter related to the media being taught. Meanwhile, the majority of 9 out of 11 students are correct in writing lyrics with good English vocabulary, with an average of 70% of the total vocabulary of the lyrics that the teacher has played. This means that the students’ vocabulary knowledge can be related to students writing achievement. The result of interview suggests that song using game media is effective in enhancing students’ English language vocabulary and writing abilities. It is to say that students' vocabulary increases after learning English with songs using games as a medium of learning.